From genes to plants via meristems. - Hay, A; Tsiantis, M (2005)
The Society for Experimental Biology organised a "Plant Frontier" meeting, which was recently held at the University of Sheffield, UK. One of the sessions of this broad meeting was on plant meristems, which covered a range of topics, including stem cells, patterning, long distance signalling and epigenetic regulation of meristem development.